2001
DOI: 10.1159/000051258
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Medial and Lateral Temporal Lobe Atrophy in Dementia with Lewy Bodies and Alzheimer’s Disease: Magnetic Resonance Imaging Volumetric Study

Abstract: Objectives: To compare medial and lateral temporal lobe atrophy on magnetic resonance imaging (MRI) in dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD), and to examine the relationship between volumetric indices and cognitive and non-cognitive symptoms. Methods: T1-weighted 1.0-tesla MRI scans were acquired in elderly subjects with DLB (n = 26; mean age = 75.8 years) and AD (n = 22; 77.3 years) and normal controls (n = 26; 76.2 years). MRI-based volume measurements of the hippocampus, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 32 publications
(40 reference statements)
6
46
2
3
Order By: Relevance
“…In general, DLB patients show less severe episodic memory deficits than AD patients, despite suffering similar levels of dementia. This is consistent with previous studies (e.g., Barber, McKeith, Ballard, Gholkar, & O'Brian, 2001) indicating that the medial temporal structures involved in memory are more severely affected in AD than in DLB. The literature on implicit memory indicates that the observed pattern of results (Heindel et al, 1989) also differentiates patients with subcortical and cortical dementias.…”
Section: Discussionsupporting
confidence: 93%
“…In general, DLB patients show less severe episodic memory deficits than AD patients, despite suffering similar levels of dementia. This is consistent with previous studies (e.g., Barber, McKeith, Ballard, Gholkar, & O'Brian, 2001) indicating that the medial temporal structures involved in memory are more severely affected in AD than in DLB. The literature on implicit memory indicates that the observed pattern of results (Heindel et al, 1989) also differentiates patients with subcortical and cortical dementias.…”
Section: Discussionsupporting
confidence: 93%
“…182 This volume loss was also significantly greater in demented patients compared with both cognitive impaired and elderly control subjects. Similarly, Grunwald et al 183 found hippocampal volume loss in dementia, and Barber et al 184 found a loss of hippocampal asymmetry in patients with dementia with Lewy bodies (DLB) (as well as AD patients) compared to normal controls. Volumetric MRI of the brain in elderly subjects with lacunes, mild cognitive impairment, a group of patients with dementia, and a group with probable AD revealed hippocampal volume loss in all three patient groups.…”
Section: Dementiamentioning
confidence: 93%
“…In AD, brain atrophy rates are significantly higher, ie, up to 2% to 3 % per year [41,42] and so are atrophy rates of hippocampus (controls, 1.0% to 1.2% per year; AD, 3.0% to 5.9% per year) and in entorhinal cortex (controls, 1.4% to 2.9% per year; AD, 7.1% to 8.4% per year [31,37], ie, structures known to be affected early in AD. Although there is some overlap between the brain regions with the most pronounced atrophy in AD and atrophied brain in other types of dementia, degree of atrophy and pattern of involved brain areas seem to be sufficiently different to allow for a differentiation between various forms of dementia, eg, Lewy Body Disease, Parkinson's disease with dementia, fronto-temporal lobe dementia [43][44][45][46][47][48][49][50].…”
Section: Structural Neuroimagingmentioning
confidence: 99%